2015
DOI: 10.1002/hbm.22736
|View full text |Cite
|
Sign up to set email alerts
|

Reduced functional connectivity in the thalamo‐insular subnetwork in patients with acute anorexia nervosa

Abstract: The neural underpinnings of anorexia nervosa (AN) are poorly understood. Results from existing functional brain imaging studies using disorder-relevant food- or body-stimuli have been heterogeneous and may be biased due to varying compliance or strategies of the participants. In this study, resting state functional connectivity imaging was used. To explore the distributed nature and complexity of brain function we characterized network patterns in patients with acute AN. Thirty-five unmedicated female acute AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
66
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 93 publications
11
66
3
Order By: Relevance
“…Less cortical folding could, in turn, increase vulnerability to AN by disrupting communication between and/or within networks subserving self-concept formation and appropriate response selection (Medford & Critchley, 2010), particularly in the context of energy homeostasis. Again, altered resting-state functional connectivity, consistent with this hypothesis, has been reported in AN; Ehrlich et al (2015) reported reduced resting-state functional connectivity within a thalamo-insular subnetwork in acute AN, and Gaudio, Olivo, Zobel & Schiöth (2018) reported reduced resting-state functional connectivity within a cerebellar-insular-parietal-cingular subnetwork in acute AN.…”
Section: Distinct Associations Between Core An Symptomatology and Sitsupporting
confidence: 78%
“…Less cortical folding could, in turn, increase vulnerability to AN by disrupting communication between and/or within networks subserving self-concept formation and appropriate response selection (Medford & Critchley, 2010), particularly in the context of energy homeostasis. Again, altered resting-state functional connectivity, consistent with this hypothesis, has been reported in AN; Ehrlich et al (2015) reported reduced resting-state functional connectivity within a thalamo-insular subnetwork in acute AN, and Gaudio, Olivo, Zobel & Schiöth (2018) reported reduced resting-state functional connectivity within a cerebellar-insular-parietal-cingular subnetwork in acute AN.…”
Section: Distinct Associations Between Core An Symptomatology and Sitsupporting
confidence: 78%
“…Consistent with our findings, Favaro and colleagues also reported decreased connectivity in both acute and recovered AN within the visual network, in a region also associated with visual perception of the body (30). In a study using a network-based statistical approach, Ehrlich and colleagues found decreased connectivity in a thalamo-insular subnetwork including the fusiform gyrus, which might explain the disturbance in homeostatis and perceived body state in AN (55). Our results, together with previous literature, suggest that brain circuits associated with body image processing are dysfunctional in AN, and may underpin features such as distorted body image perception and abnormal experience of the body, characteristic of AN.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal ACC-insular resting state activity has also been observed in ED patients (Amianto et al, 2013; Dunlop et al, 2015b). Altered connectivity strength and path length between the insula and thalamus has been observed in AN (Geisler et al, 2016), as well as decreased functional connectivity between the thalamus, putamen and insula (Ehrlich et al, 2015). Given all this evidence, the variation in symptoms across different classes of EDs—for example, the presence of binging behavior in BN and BED, but not AN—make it difficult to assess convergent implicated brain regions, and both structural gray matter and functional activity analyses in these populations should be expanded (Schäfer et al, 2010).…”
Section: Abnormalities Of Sn-cstc Loop Circuits In Psychiatric Illnessesmentioning
confidence: 99%